2010
DOI: 10.1016/j.catcom.2009.11.023
|View full text |Cite
|
Sign up to set email alerts
|

BiOX (X = Cl, Br, I) photocatalysts prepared using NaBiO3 as the Bi source: Characterization and catalytic performance

Abstract: The Bismuth oxyhalides, crystalline BiOX (X = Cl, Br, I) were prepared via a facile method, using NaBiO 3 25 and HX aqueous solutions as the raw materials for the first time. The systematic microstructure and opti-26 cal property characterizations of the BiOX photocatalysts demonstrated the reliability of this new and 27 facile preparation approach. The photocatalytic activity on the degradation of typical phenolic endocrine 28 disrupting chemicals over BiOX and P25 were evaluated under Xenon-light irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
116
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(135 citation statements)
references
References 17 publications
4
116
1
5
Order By: Relevance
“…7a), indicating that the BiOBr is an excellent visible − light-response photocatalyst, as reported earlier. Again, no degradation of SA is observed in the BiOI system under either visible-light and UV irradiation, which is different from the results in previous reports (Chang et al, 2010;Qin et al, 2013;Zhang et al, 2008b), where it was reported that BiOI had the highest activity among BiOXs. Considering the narrow band gap and strong visible light absorption of BiOI, its inactivity in photocatalytic degradation is somewhat striking in our study.…”
Section: Characterization Of Bioxscontrasting
confidence: 99%
See 2 more Smart Citations
“…7a), indicating that the BiOBr is an excellent visible − light-response photocatalyst, as reported earlier. Again, no degradation of SA is observed in the BiOI system under either visible-light and UV irradiation, which is different from the results in previous reports (Chang et al, 2010;Qin et al, 2013;Zhang et al, 2008b), where it was reported that BiOI had the highest activity among BiOXs. Considering the narrow band gap and strong visible light absorption of BiOI, its inactivity in photocatalytic degradation is somewhat striking in our study.…”
Section: Characterization Of Bioxscontrasting
confidence: 99%
“…Since the most famous wide-band-gap (3.2 eV) photocatalyst TiO 2 cannot utilize sun light efficiently, BiOX semiconductors have attracted much attention as a class of promising photocatalysts due to their special structural and optical properties, with band gaps of approximately 3.2, 2.6 and 1.7 eV for BiOCl, BiOBr and BiOI powders (Chang et al, 2010;Qin et al, 2013;Zhang et al, 2008b), respectively, and can be excited by UV and/or visible light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al employed a gel technique to obtain 5 mm long BiSI single crystals. 13 On the other hand, BiOI (the same V-VI-VII class compound) has widely been studied in recent years, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] especially because of a high catalytic activity in the visible region. BiOI has been reported to show a high photocatalytic activity for photodegradation of an organic dye under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Various synthesis methods leading to BiOX have been reported, such as hydrothermal [15][16][17][18], transformation from NaBiO 3 [19], hydrolysis [20], homogenous deposition [21] and reverse microemulsions [22], which displayed different photoactivities of BiOX. Homogenous deposition is a simple way for the preparation of BiOX that has a plate structure, with high surface area, which facilities the adsorption of dyes and photocatalytic processes.…”
mentioning
confidence: 99%